An Integrated Channel Coding and Cryptography Framework for Secure and Energy-Efficient Wireless Energy Data Transmission - Zheng, Yan; Liu, Xingbo; Ye, Lei; Yu, Mingjun; Wen, Yi (Informatica, 2025)
This paper proposes a secure and energy-efficient wireless energy data transmission framework that integrates channel coding algorithms with cryptographic techniques. The framework employs LDPC codes, Turbo codes, and polar codes for channel coding, combined with AES, RSA, ECC, PRESENT, and SIMON cryptographic algorithms to address interference, information monitoring, and energy constraints in wireless environments. A dynamic power control strategy based on a greedy algorithm and a channel adaptive coding scheme are designed to optimize energy consumption and transmission reliability. Experiments were conducted using the NS3 simulation platform (with 50 nodes in a grid topology, simulated over 1000 seconds) and a small-scale field test. Key parameters included noise levels set at -90dBm to -60dBm, packet sizes of 512 bytes (AES/RSA) and 256 bytes (PRESENT/SIMON), and initial node energy levels of 1000mJ. Results show that compared with conventional algorithms, the proposed framework reduces the bit error rate by 15.3% (baseline: traditional channel coding without encryption) and energy consumption by 8.7% (baseline: standard WSN routing protocols). Specifically, it achieves a 44.6% lower energy consumption, 30.8% shorter transmission delay, and 73.3% lower bit error rate than traditional models, demonstrating superior performance in secure and efficient energy data transmission.